EFEKTIVITAS TERAPI MELUKIS DAN MENGGAMBAR PADA PASIEN SKIZOFRENIA - Wulan, Winda Ratna (Yayasan Healing and Healthcare Education, 2025)
The World Health Organization states that there are approximately 23 million people with schizophrenia worldwide. The positive and negative symptoms experienced by patients with schizophrenia can significantly affect their ability to engage in activities, build relationships, and live independently. Art therapy, as part of a therapeutic modality, serves as a therapeutic intervention and can be used as a tool to provide psychological insights and promote emotional maturity. Painting or drawing can visualize symbols that emerge from the subconscious as expressions of the patients.The research method involved electronic searches using databases such as PubMed Health, ScienceDirect, and CrossRef, with the keyword